Pengembangan Soal Matematika Serupa Pisa Dalam Konten Change And Relationship Pada Siswa Kelas VIII - Triharyati, Nunik, Prof. Dr. Budi Murtiyasa, M.Kom (2015)
This research aims to design and develop the PISA math problems similar change in the content and relationship in the eighth grade. The model used in this research is the development research (research and development). which consists of two stages, there are two stages in this study is preliminary and formative stage of evaluation that includes self evaluation, expert reviews and one-to-one (low resistance to revision) and a small group and field test (hight resistance in revision). Data collection techniques used by the walkthrough, document analysis and tests. During through stage one-to-one to small group, validated by qualitative descriptive matter after it tested to the field test stage. Research subjects are students of class VIII E SMPN 1 Kerjo. The test results with the average value of reasoning ability for reproduction 59.3 competencies included in both categories, with 44.3 connections competence included in the category enough and to competence 35.8 reflections included in the category enough. According the average score in each competency can be seen that the matter was appropriate level of competence. From these results it can be said that the PISA math problems similar in content and relationship change has potential effects on students' mathematical reasoning abilities.